Analysis of Quality of Pharmacy Management Information System at Sultan Agung Islamic Hospital, Semarang - Rosyid, Abdur; Marchaban, Marchaban; Pudjaningsih, Dwi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2021)
Introduction: Hospital is one of the important links in the service delivery system to the community so that the hospital is expected to provide information to support the provision of timely and accurate services. To improve the quality of hospital services, an up to date information system is needed. The user satisfaction on information system can be used to evaluate the quality of an organization's information system. Objective: to evaluate the quality of the pharmacy management information system (PMIS) at Sultan Agung Islamic Hospital (SAIH), Semarang, and determine the priority of area for improvements.Methods: In this cross-sectional qualititative study, the responses of all employees to questionnaire were obtained; these employees worked at the pharmacy of Sultan Agung Islamic Hospital in Semarang. The PIECES method was applied. The data analysis included gap and customer windowResults: The gap value on the dimension of performance, information, economic, control, efficiency, service was -1.10, -0.82, -0.28, -0.22, 0.01, -0.62, respectivelyConclusion: The user’s unfulfilled expectation on PMIS at SAIH including dimensions of performance, information, economy, control, service, and efficiency. Priority areas for quality improvement of PMIS at the Sultan Agung Islamic Hospital’s phamacy included the menu display, system responsiveness, the completeness of the system, no error occurs, the alert system of the drug stock, the responsiveness of the IT department to the problem of PIMS use.